Especificaciones técnicas para el uso de piel en indumentaria, para Cueros RJ de la ciudad de Ambato - Alomaliza Paucar, Anabel Paola (2025)
The textile and leather industries in Ecuador represent a significant pillar of the national economy, playing an essential role in the country’s economic development and productive transformation. However, this sector faces critical challenges, such as the lack of standardization and specific technical guidelines to ensure the quality and competitiveness of leather products used in apparel. In the context of Ambato, a city renowned for its artisanal tradition and its importance in leather production and commerce, this issue becomes particularly pressing. This research addresses these limitations by proposing the development of a technical guide that establishes clear specifications for the use of leather in garment manufacturing. This work aims not only to standardize practices but also to foster innovation, improve product quality, and strengthen the competitive position of local companies like Cueros RJ, aligning with international regulations and the demands of a globalized market. Through an integrative approach that combines bibliographic research, interviews with key industry stakeholders, and technical analysis via normative data sheets, this project will contribute to the sustainable development of the leather industry. Additionally, it will benefit designers, manufacturers, and small producers by ensuring the creation of products that meet high-quality standards and promoting a culture of excellence within the sector